2021
DOI: 10.3390/s21144874
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Robotic Exoskeleton-Assisted Gait Training in Spinocerebellar Ataxia: A Case Report

Abstract: Spinocerebellar ataxia (SCA) is a hereditary neurodegenerative disorder that presents as ataxia. Due to the decline in balance, patients with SCA often experience restricted mobility and a decreased quality of life. Thus, many studies have emphasized the importance of physiotherapies, including gait training, in SCA patients. However, few studies have examined the effectiveness of robotic gait training in SCA. Here, we report the therapeutic outcomes of exoskeleton-assisted gait training in a patient with SCA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Our results are in line with recent literature [ 28 , 31 , 32 , 33 ], encouraging RAGT treatment in patients with ataxia. Particularly, a close correspondence can be found with the work of Kim et al [ 28 ], in which a patient with SCA6 underwent 24 sessions of training in the use of an exoskeleton; authors reported an improvement of the SARA scale, greater balance at the Berg scale, greater distance at the 10 MWT, and an improved gait cycle. All these findings are confirmed in our experience.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are in line with recent literature [ 28 , 31 , 32 , 33 ], encouraging RAGT treatment in patients with ataxia. Particularly, a close correspondence can be found with the work of Kim et al [ 28 ], in which a patient with SCA6 underwent 24 sessions of training in the use of an exoskeleton; authors reported an improvement of the SARA scale, greater balance at the Berg scale, greater distance at the 10 MWT, and an improved gait cycle. All these findings are confirmed in our experience.…”
Section: Discussionsupporting
confidence: 93%
“…Among currently available therapeutic options, rehabilitation assumes a huge importance; in particular, it is widely recognized that, through movement assistance provided by an exoskeleton, both the muscular and nervous system are stimulated where they are deficient, and thus predict an improvement in impaired function [28]. Movements produced by an exoskeleton not only represent an action, but also an idea, a new mode of motor planning [28] in which the intention has the same importance as the action. It is known that motivation, involvement [29], and positive patient feedback [30] are needed for rehabilitation success, to improve robotic technology as a resource Coming to our results discussion, the patient showed an improvement in the functional items of the SARA and BBS scales, relating to the static balance in standing, dynamic during postural transitions and walking; these improvements lead to hypothesize better motor control during walking, as well as a greater ability to carry out ADLs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that these patients could walk more smoothly with an increased harmonic ratio while walking with the wearable robot system than without the system. In addition, other studies have demonstrated improvements in gait function and postural balance after weeks of RAGT with the wearable robot system in patients with spinocerebellar ataxia [ 29 , 30 ]. These findings suggest the potential benefit of over-ground RAGT for patients with ataxia.…”
Section: Discussionmentioning
confidence: 99%